Do physical activity and screen time mediate the association between European fathers' and their children's weight status? Cross-sectional data from the Feel4Diabetes-study - Julie Latomme; Nele Huys; Greet Cardon; Philip J. Morgan; Mina Lateva; Nevena Chakarova; Jemina Kivelä; Jaana Lindström; Odysseas Androutsos; Esther M. González-Gil; Pilar De Miguel-Etayo; Anna Nánási; et al. (BMC, 2019)
Abstract Background Most research on parenting and childhood obesity and obesity-related behaviours has focused on mothers while fathers have been underrepresented. Yet, recent literature has suggested that fathers uniquely influence their children's lifestyle behaviours, and hence could also affect their weight status, but this has not yet been scientifically proven. Therefore, the present study aimed to determine whether the association between fathers' weight status and their children's weight status is mediated by fathers' and children's movement behaviours (i.e. physical activity (PA) and screen time (ST)). Methods Cross-sectional data of 899 European fathers and their children were analyzed. Fathers/male caregivers (mean age = 43.79 ± 5.92 years, mean BMI = 27.08 ± 3.95) completed a questionnaire assessing their own and their children's (mean age = 8.19 ± 0.99 years, 50.90% boys, mean BMI zscore  = 0.44 ± 1.07) movement behaviours. Body Mass Index (BMI, in kg/m2) was calculated based on self-reported (fathers) and objectively measured (children) height and weight. For children, BMI z-scores (SD scores) were calculated to obtain an optimal measure for their weight status. Serial mediation analyses were performed using IBM SPSS 25.0 Statistics for Windows to test whether the association between fathers' BMI and children's BMI is mediated by fathers' PA and children's PA (model 1) and fathers' ST and children's ST (model 2), respectively. Results The present study showed a (partial) mediation effect of fathers' PA and children's PA (but not father's ST and children's ST) on the association between fathers' BMI and children's BMI (model for PA; coefficient: 0.001, 95% CI: [0.0001, 0.002]; model for ST; coefficient: 0.001, 95% CI: [0.000, 0.002]). Furthermore, fathers' movement behaviours (PA and ST) were positively associated with their children's movement behaviours (PA and ST) (model for PA, coefficient: 0.281, SE: 0.023, p < 0.001; model for ST, coefficient: 0.345, SE: 0.025, p < 0.001). Conclusions These findings indicate that the influence of fathers on their children's weight status partially occurs through the association between fathers' PA and children's PA (but not their ST). As such, intervening by focusing on PA of fathers but preferably of both members of the father-child dyad (e.g. engaging fathers and their children in co-PA) might be a novel and potentially effective strategy for interventions aiming to prevent childhood overweight and obesity. Longitudinal studies or intervention studies confirming these findings are however warranted to make meaningful recommendations for health intervention and policy. Trial registration The Feel4Diabetes-study is registered with the clinical trials registry http://clinicaltrials.gov, ID: 643708.